Netizen Journalism and the Democratization of Local News: A Case Study of @abouttng on Instagram in Tangerang, Indonesia - Widianti, Mira Adita; Pramana, Pramana; Srikandi, Melati Budi (Universitas Ahmad Dahlan, 2025)
The rise of social media has transformed the production and distribution of news, giving birth to participatory models of journalism often referred to as netizen journalism. This study investigates the role of the Instagram account @abouttng as a platform for local information dissemination and civic engagement in Tangerang, Indonesia. Using a qualitative content analysis approach, the research examines @abouttng’s use of visual media, interaction patterns, and thematic content—focusing on topics such as infrastructure, transportation, environmental concerns, and public safety. The findings reveal that @abouttng functions not only as an alternative news outlet but also as a participatory space where netizens act as content producers, commentators, and civic advocates. Visual storytelling enhances content credibility and reach, while active user engagement facilitates real-time discourse and collective problem-solving. The study highlights both the democratic potential and ethical challenges of decentralized information environments, including issues of misinformation, content moderation, and the absence of traditional editorial oversight. By expanding on the theoretical framework of participatory journalism, this research provides insight into how hyperlocal social media accounts contribute to grassroots communication ecosystems, community awareness, and digital civic engagement in the Global South.